2019
DOI: 10.1186/s12885-019-5326-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic markers of distant metastases and poor prognosis in gynecological cancers

Abstract: BackgroundDespite the recent progress in the development of anti-cancer drugs, the treatment of metastatic tumors is usually ineffective. The systemic inflammatory response performs key roles in different stages of the carcinogenesis process including metastasis. The high neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), and platelet-lymphocyte ratio (PLR) were found to be associated with poor survival rates in the majority of solid tumors. However, only a few studies were conducted to furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
30
1
2
Order By: Relevance
“…Neutrophil secretes vascular endothelial growth factor (VEGF) and proteases, such as matrix metalloproteinase and elastase enzymes, causing cancer cells to invade and metastasize. Monocytes also increase cancer cell migration and inhibit immunity to the tumor cell (12). Although there was no statistically significant difference in our study, it was thought that the high level of monocyte value might be important for the response to the tumor.…”
Section: Figure 1 Kaplan-meier Analysis Of Median Progression-free Scontrasting
confidence: 61%
“…Neutrophil secretes vascular endothelial growth factor (VEGF) and proteases, such as matrix metalloproteinase and elastase enzymes, causing cancer cells to invade and metastasize. Monocytes also increase cancer cell migration and inhibit immunity to the tumor cell (12). Although there was no statistically significant difference in our study, it was thought that the high level of monocyte value might be important for the response to the tumor.…”
Section: Figure 1 Kaplan-meier Analysis Of Median Progression-free Scontrasting
confidence: 61%
“…Some previous articles reported that the distributions of serum inflammation markers were different between metastatic and non-metastatic tumors (15). Thus, we first evaluated the distributions of NLR, PLR, LMR, SII index, lymphocyte count, monocyte count and neutrophil count between liver metastatic and non-metastatic pNENs, and statistical analysis indicated that none of these markers distributed differently between the two groups ( Supplementary Fig.…”
Section: Marker Selection and Cut-off Point Definitionmentioning
confidence: 99%
“…For FIGO stages, I and II were defined as early stage, while III and IV were defined as advanced stage. 10,12…”
Section: Data Analysis and Definitionsmentioning
confidence: 99%
“…5 In addition, a growing body of evidence has found that platelets also play a role in tumor cell growth, metastasis, and angiogenesis. 6,7 Decades of studies indicated that platelet indicators are important prognostic factors in patients with different types of cancer, such as gynecologic cancers, [8][9][10][11][12][13] lung cancer, 14,15 gastric cancer, 16 colorectal cancer, 5 pancreatic cancer, 17,18 laryngeal cancer, 19 and rectal cancer. 20 Thrombocytosis may precede the diagnosis of malignancy.…”
Section: Introductionmentioning
confidence: 99%